2018
DOI: 10.1128/aem.00004-18
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variation in the Bacterial Community Associated with Airborne Particulate Matter in Beijing, China, during Hazy and Nonhazy Days

Abstract: The structural variation of the bacterial community associated with particulate matter (PM) was assessed in an urban area of Beijing during hazy and nonhazy days. Sampling for different PM fractions (PM [<2.5 μm], PM [<10 μm], and total suspended particulate) was conducted using three portable air samplers from September 2014 to February 2015. The airborne bacterial community in these samples was analyzed using the Illumina MiSeq platform with bacterium-specific primers targeting the 16S rRNA gene. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 78 publications
(94 reference statements)
3
28
1
1
Order By: Relevance
“…Many studies have confirmed the influence of atmospheric dust-associated trace elements on the airborne prokaryotic community (Yan et al, 2018;Zhai et al, 2018;Romano et al, 2020). However, there was no clear correlation between APC structure and the trace elements contained in the onshore and offshore atmosphere over the Red Sea as shown in the PCA biplots.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed the influence of atmospheric dust-associated trace elements on the airborne prokaryotic community (Yan et al, 2018;Zhai et al, 2018;Romano et al, 2020). However, there was no clear correlation between APC structure and the trace elements contained in the onshore and offshore atmosphere over the Red Sea as shown in the PCA biplots.…”
Section: Discussionmentioning
confidence: 99%
“…In order to mine deeper data of microbial diversity of the difference among the four groups, significance test was conducted with linear discriminant analysis effect size (LEfSe, http://huttenhower.sph.harvard.edu/galaxy). The network was generated using the CoNet plugin (version 1.1.1) for Cytoscape (version 3.6.1) on the basis of the nonparametric Spearman correlation coefficients, with a minimal cutoff threshold rho of 0.6 (p < 0.05, Benjamini–Hochberg corrected) (Yan et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Geobacillus is a known thermo-resistant, spore-forming, ubiquitous Firmicute (Zeigler 2014). Tumebacillus (aerobic, spore-forming, gram-positive, rod-shaped, chemolithoautotroph) has been found in high Arctic Canadian permafrost (Steven et al 2008) and was identified as one of the most abundant lineages in Australian dry lake aerosols (Munday et al 2016) and heavy-haze days in Beijing, China (Yan et al 2018). Firmicutes are recurrently characterized as highly abundant in free tropospheric air masses and longrange transport air masses (Smith et al 2011David et al 2018;Els et al 2019) and were enhanced in free tropospheric fall samples (Bowers et al 2012).…”
Section: Different Seasonal Dispersal Patterns For Bacterial and Fungmentioning
confidence: 99%